Children saving lives: Training towards CPR excellence levels in chest compression based on age and physical characteristics. (December 2017) - Mpotos, Nicolas; Iserbyt, Peter
Abstract: Background: The World Health Organization's endorsement of the "Kids save lives" statement fosters the implementation of cardiopulmonary resuscitation (CPR) training for school children worldwide. However, not every child achieves and maintains the recommended chest compression depth of 5–6 cm. Purpose: To investigate the variability in compression depth for three age groups (grade 1: 12–14; grade 2: 14–16; grade 3: 16–18 years) as a function of physical characteristics and to define minimal compression excellence levels for training. Methods: Compression depth of 265 subjects (111 girls, 154 boys) aged 12–18 years from one secondary school was individually assessed and reported in percentiles per age group. Pearson correlations between physical characteristics and CPR variables were calculated. Excellence level was defined as the percentage compressions with depth 5–6 cm. Results: In grade 1 (12–14 years), achieved excellence levels were 1% for girls and 23% for boys at the 75th percentile. In grade 2 (14–16 years), it increased to 24% for girls and 80% for boys. In grade 3 (16–18 years) finally, it was 59% for girls and 87% for boys. Significant positive correlations were found between CPR and physical variables (p < 0.05), especially weight >50 kg (p < 0.01). Conclusion: A minimal excellence level of 25% is achievable by boys 12–14 year and girls 14–16 year and can be gradually improved to 60% and 90% according to age and gender. This might necessitate more exertion and training for some younger children, especially girls, and will probably be more easily achieved for children weighing >50 kg.